L’autobiographie ou l’art de la vie dans A Small Boy and Others de Henry James - Thomas Constantinesco; Agnès Derail (Transatlantica)
Although Henry James always maintained that “it is art that makes life,” he did start writing his autobiography in the last years of his life, telling the story of his calling as a writer under cover of paying tribute to his brother William’s genius. The tension between self and other is at the core of James’s autobiographical project, which consists paradoxically in looking for oneself the better to lose oneself. A Small Boy and Others thus repeats and compounds the small boy’s experience of life as nonlife. Yet in withdrawing from his own life, James leaves it to be re-imagined and recreated, so that his evasion from life allows him to develop his capacity for wonder and to become a vessel for the manifold impressions to which his consciousness is exposed and which he transforms into a series of scenes that make up his life. In the end, however, far from coalescing into a consistent and meaningful whole, the multiplicity of impressions disorients the teleological effort underlying James’s autobiography and exposes the very otherness that is constitutive of selfhood. For James then, writing his life as “a small boy” means ultimately telling the story of his being haunted by the “others” that his title hints at and whose inescapable presence around and within him contributes to making and unmaking his sense of self.